Study on the influence of sudden load at idle condition on vibration and vibration isolation performance of the engine mount system. (April 2023) - Luo, Fuqiang; Wu, Shaozhe; Ding, Xinhua; Zhou, Jing; Zhou, Zhifeng; Han, Yubin
Engine vibration is one of the main excitation sources of vehicle vibration. In order to study the problem of excessive vibration in the cabin of a light vehicle when the air conditioning is turned on at the idle speed, this study is conducted from the point of view of in-cylinder combustion caused by sudden load. The vibrations of the engine with the air conditioning on and off at the idle condition were studied experimentally. The results show that when the air conditioning is turned on at low idle speed, the cylinder pressure rise rate increases with the increase of fuel injection. In addition, the combustion pressure in the cylinder also increases, which leads to the increase of engine vibration. At the same time, a spectrum analysis is carried out in terms of the vibration signal in the maximum direction of the vibration intensity of the suspension system, and the vibration isolation rate is calculated. The results show that the vibration intensity at the second order is the largest, and the vibration isolation effect of the rear suspension is poor.